2020
DOI: 10.17309/jltm.2020.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Motor Skills in the Structure of Physical Fitness of 7-Year-Old Boys

Abstract: The purpose of this study was to determine the weight of motor skills in the structure of motor fitness of 7-year-old boys.  Materials and methods. The study participants were 38 7-year-old boys. The children and their parents were informed about all the features of the study and gave their consent to participate in the experiment. The research methods used in the study include analysis of scientific and methodological literature, pedagogical observations, testing of motor fitness, probabilistic approach to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
5
13
0
2
Order By: Relevance
“…The obtained results supplement the data on the relationship between the level of proficiency in gymnastic exercises and the level of development of strength and vestibular stability (Ivashchenko, Berezhna, & Cieślicka, 2020;Ivashchenko & Sirichenko, 2020). As with 7-year-old girls, there is considerable variation in the development of flexibility, arm strength, and vestibular stability.…”
Section: Componentsupporting
confidence: 72%
“…The obtained results supplement the data on the relationship between the level of proficiency in gymnastic exercises and the level of development of strength and vestibular stability (Ivashchenko, Berezhna, & Cieślicka, 2020;Ivashchenko & Sirichenko, 2020). As with 7-year-old girls, there is considerable variation in the development of flexibility, arm strength, and vestibular stability.…”
Section: Componentsupporting
confidence: 72%
“…on the level of proficiency in acrobatic exercises. The results obtained supplement the data of Ivashchenko, Berezhna, and Cieślicka (2020) who found that the level of proficiency in exercises determines the variation of testing results in 7-yearold boys by 28.437%, the development of "agility" and "movement coordination" ensures the formation of motor skills, and the development of arm strength and vestibular stability is the reserve in training 7-year-old boys that will increase the effectiveness of the educational process; and also the data of Ivashchenko and Sirichenko (2020), according to which the level of proficiency in exercises determines the variation of testing results in 7-year-old girls by 29.772%. A discriminant analysis revealed the indicators that have the greatest weight in assessing gender-related peculiarities of motor fitness of 7-year-old schoolchildren.…”
Section: Discussionsupporting
confidence: 85%
“…300 m running (s)", 5 -"30 m sprint running from a standing start (s)", 6 -"Seated forward bend (cm)", 7 -"Mixed hang rope pull-ups (times)", 8 -"Shuttle run 4×9 m (s)", 9 -"Combined movements of arms, torso and legs (points)", 10 -"Maintenance of stable posture -standing on one leg with closed eyes (s)", 11 -"Walking along straight line after 5 rotations (deviations in cm)", 12 -"Rope climbing in two steps, level of proficiency". 13 -"Rope climbing in three steps, level of proficiency", 14 -"One leg swing upward circle, level of proficiency" the level of motor abilities development (Ivashchenko, Berezhna, & Cieślicka, 2020;Ivashchenko & Sirichenko, 2020). The results of factor analysis confirm the integrity of the process of motor skills formation and motor abilities development in children and supplement the data of Khudolii, Ivashchenko, and Chernenko(2015); Ivashchenko, Iermakov, Khudolii, Cretu, and Potop (2017).…”
Section: Discussionmentioning
confidence: 65%